The Marriage System in Modern Society as Exposed by the Women Moral and Spiritual Breakdown in Shobha De's Novels: Exploring the Impact of Marriage on Society through Shobha De's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The biological definition of marriage described in this article demonstrates the importance ofmarriage to human society regardless of whether or not it has been recognized by the state or the church.As a lifetime commitment between a woman and husband, marriage is considered one of the Sanskaras(sacraments) in India. Marriage in Hinduism is a solemn contract between a man and a woman in whichboth parties pledge to support one another in their pursuit of Dharma, Artha, Kama, and Moksha. Assuch, it affects the social and cultural development of society by providing access to the pleasures ofearthly life, the hope of future improvement, and the care of the next generation.